Muslims Are Not Moral Agents: A Study of Religious Crossshijaber in Social Media Islamic Psychological Perspective and Relevance with Religious Moderation in Indonesia - Wasilah, Wasilah; Purnawan, Adam Rizki; Al Asy’ari, M Khoirul Hadi (Proceeding International Conference on Religion, Science and Education, 2024)
This research investigates the role and impact of religious micro-celebrities on social media, specifically focusing on the context of Muslim women. In an increasingly digitally connected society, religious influencers have become significant players in sharing religious messages and moral values. However, this study explores whether the perception that they are “moral agents” has an empirical basis in a cultural psychology perspective. With an interdisciplinary approach, this research combines elements of Islamic psychology and its relevance to religious moderation in Indonesia, social media, and religious studies. We see how religious micro-celebrities influence the perceptions and behavior of their followers in adopting religious values in their daily lives. Additionally, we examine the impact of social media as a tool that facilitates the transformation of culture and religious values. In our analysis, we highlight how social media use by religious celebrities influences individual religious identities and cultural dynamics in Muslim societies. We also explore how these influences may influence common understandings of morality and ethics in an increasingly complex digital world. The results of this study provide insight into the role and impact of religious crosshairs on social media, highlighting that Muslim women are not sole moral agents. This study reminds us to understand the complexity of the social and psychological dynamics behind religious social media and stimulates reflection on our role as consumers of information and values in an increasingly connected digital world. In conclusion, this research provides a valuable contribution to our understanding of the phenomenon of religious celebrities in this digital era. There are two important questions in this research, first, what is the concept of religious crossjaber on social media? and secondly, what is the view of Islamic psychology and religious moderation on the phenomenon of religious cross-hijaber on social media? using an Islamic psychology approach to explain this study and one of the research results states that there are limitations and limitations to the crosshijaber phenomenon on social media.